The dyeing properties of natural cotton fabric. (June 2015) - Wang, Y.; Chen, D. S.; Lin, X.; Wang, W. Z.
<x content-type="archive" xml:space="preserve">Abstract</x> The cotton is one of representative natural fibres. By choosing the cotton fabric as the subject, this paper mainly discusses the impact of different dye quality, temperature of dye solution, dyeing time, bath ratio and salt quantity during the dyeing on the dye uptake and colour fastness, in order to find the optimal formula of dye solution. Samples are treated using the orthogonal experiment. Different levels of different factors are evenly divided into 25 groups. Results of each group are compared and analysed. According to the statistical analysis, it can confirm formula with the highest dye uptake and colour fastness. By balancing the amount of the both and considering the cost-saving as far as possible, it thus obtains the optimal formula. Finally, it proves the correctness of experimental results according to the comparison with the formula with the empirical parameters.